Ocimum gratissimum (Linn) leaves extract attenuates oxidative stress and liver injury in gentamicin-induced hepatotoxicity in rats. Issue 1 (1st January 2021) - Ogundipe, Oluwadare J.; Akinpelu, Omolola F.; Oyerinde, Abiodun.; Oluwakemi, Oyelade R.
ABSTRACT: The adverse effect of gentamicin on tissues like kidney and liver makes its use limited in clinical settings. Ocimum gratissimum are known for many medicinal uses. The effect of aqueous extract (AOGL) and methanolic extract (MOGL) of Ocimum gratissimum (Linn) on liver following injury induced by gentamicin was investigated in this study. Forty adult (40) male Wistar rats were divided into 8 groups as follows: Group 1 (n = 5) received distilled water daily by oral route. Groups 2, 3, 4, 5, 6, 7 and 8 (n = 5) received 100 mg/kg/day of gentamicin i.p. for a week. After, groups 3, 4, 5, 6, 7 and 8 (n = 5) received 100, 200 and 400 mg/kg/day of AOGL and MOGL p.o, respectively, for 28 days. The rats treated with both AOGL and MOGL for 28 days were left for a recovery period of 14 days. Liver enzymes (ALT, AST and ALP), total bilirubin and total protein were determined in the plasma. TBARS and GSH levels were assayed in the liver homogenate. Gentamicin increases ALT, AST, ALP, total bilirubin and total protein, TBARS and decreases GSH, catalase and SOD of the toxic control when compared to the control group. Post-treatment with AOGL and MOGL in the treated groups caused increases GSH, catalase and SOD and decreases TBARS, ALT, AST, ALP, total bilirubin and total protein when compared with the toxic control group. The results show that AOGL and MOGL are capable of ameliorating liver injury caused by gentamicin in rats.